GISAKE METHOD DEVELOPMENT (SOCIAL ECONOMIC RESEARCH METHOD) - Syaiful Amri; Dedy Febry Rachman; Khaerul Hadi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This development research aims to produce a product of socio-economic research methods: 1). Learning tools, 2). Learning assessment/evaluation guidelines, 3). The product of the socio-economic research method is based on the identification of learning objectives by considering the curriculum that has been applied, namely the development of material from the 2013 curriculum on the material "designing and conducting socio-economic research", the socio-economic research method focuses on one material only, and cannot be applied to a different method. the same for other subject matter.The product that has been developed is then carried out by an expert validation test process, individual trials, small group tests and field tests. Based on the test results, the socio-economic research method is very valid, interesting, and effective and can be applied in classroom learning. This can be seen from the results of the validation test with the product feasibility level from each material expert of 90%, the product is effectively used with an average percentage score of 91%. The results of the small group product trial were found to be 87% and the class trial was carried out after going through the stages of being feasible to be applied in a classroom learning. The results of the pretest and posttest trials were found to be quite satisfactory with an achievement level of value of 100%, which indicates that this product is able to boost student interest and learning outcomes in this case using a development product in the form of the GISAKE socio-economic research method in the socio-economic research design material.This method can also be used for a wider audience with adjustments, especially adjustments to the characteristics of students as users. Furthermore, the GISAKE Socio-Economic research method that has been developed can be integrated with the use of renewable information and communication technology.